Enhancement of rice and wheat seed germination and seedling vigor by biocontrol agent, Cladosporium cladosporioides (Research in Agriculture Livestock and Fisheries, 2020)
The biocontrol agent, Cladosporium cladosporioides, strain BOU1 was used to evaluate the rice and wheat plant growth by germination percentage, germination index, vigor index- I and vigor index-II in rice and wheat seed. All the variables of germination and seedling vigor of rice and wheat were increased by the conidial suspension of C. cladosporioides. The rice seed treated with C. cladosporioides had the highest germination index and vigor index-I with average mean values of 8.2 and 4.5, respectively; while the treated wheat seed showed the highest germination percentage and vigor index- II with average mean values of 80.3 and 0.05, respectively. The research is concluded that the biocontrol agent C. cladosporioides improves seed germination and seedling vigor of wheat and rice, which can finally be converted into superior yield even in adverse conditions.Res. Agric., Livest. Fish.7(1): 09-15, April 2020